Prawne pojęcie producenta rolnego według ustawy o krajowym systemie ewidencji producentów, ewidencji gospodarstw rolnych oraz ewidencji wniosków o przyznanie płatności w świetle orzecznictwa - Trojanowski, Zbigniew (Wydawnictwo Naukowe UAM, 2013)
The aim of this paper is to define the concept of an agricultural producer that exists in the Act on the state system of registering producers, agricultural holdings and registering applications for subsidies, and to analyse selected judicial decisions applicable to the use of that concept in practice. The deliberations commence with an analysis of certain general issues such as: a spouse as an agricultural producer, an applicant as an agricultural producer, and an agricultural producer as a group of persons. Further, issues related to the striking off the identification number are presented and discussed. The paper concludes with an opinion that excluding an agricultural producer who is a spouse of another agricultural producer from the system of support dedicated to agricultural producers is unjustified, and ends with a postulate that the law on the state system of registering agricultural producers, agricultural holdings, and registering applications for subsidies needs to be amended.

Lo scopo delle considerazioni è quello di definire il concetto di produttore agricole nella legge sul registro nazionale dei produttori, delle aziende agricole e delle richieste di contributi, ma anche di risolvere problemi legati all’applicazione di questo concetto in pratica. Le considerazioni vengono aperte dall’analisi delle questioni più generali, in seguito l’autore esamina questioni specifiche quali: il coniuge come produttore agricolo, il richiedente come produttore agricolo e il produttore agricolo come gruppo di persone nonché i problemi legati alla rimozione del numero di identificazione. Concludendo, l’autore definisce ingiustificata l’esclusione dei produttori agricoli coniugi di un altro produttore agricolo dagli strumenti di sostegno. Le considerazioni vengono chiuse con il postulato di emendare la legge sul registro nazionale dei produttori agricoli, delle aziende agricole e delle richieste di contributi.
Legal concept of an agricultural producer under the Act on the state system of registering producers, agricultural holdings and registering applications for subsidies in light of selected judicial decisions
La nozione giuridica del produttore agricolo secondo la legge sul registro nazionale dei produttori, delle aziende agricole e delle richieste di contributi alla luce della giurisprudenza